Child Participation in Marriage Dispensation in Southeast Asian Muslim Countries from The Perspective of the Convention on the Rights of the Child - Ernawati, Ernawati; Abdullah, Abdul Gani; Subhan, Zaitunah (Journal of World Science, 2023)
The purpose of this research is to understand and analyze child marriages in Muslim-majority countries in Southeast Asia from the perspective of the Convention on the Rights of the Child. The research design used in this study is qualitative. The research nature is juridical-normative, referring to legal norms present in the legislations of Indonesia, Malaysia, and Brunei Darussalam. The research results indicate that using the CRC's concept of Child Participation in dispensations for underage marriage, it was previously shown that the concept of child protection encompasses a broad scope (O'Donnell), and the Convention on the Rights of the Child emphasizes that all actions taken concerning the child must be contextually appropriate, for the best interests of the child (Eekelaar). Therefore, this study shows to what extent the protection of children's rights regarding their participation in dispensations for underage marriage in Southeast Asian Muslim countries, is allegedly contradictory to the CRC's definitive provision on the age of the child. This research implies that it can help analyze the extent to which child marriages violate the rights of the child as guaranteed by the Convention on the Rights of the Child. It aids in understanding how cultural and religious factors influence the practice of child marriages in Muslim-majority countries in Southeast Asia. Additionally, the results of this research could stimulate further studies in the same or related domains.